The Transition from Childhood to Adolescence: Between Health and Vulnerability - Francesca Mastorci; Maria Francesca Lodovica Lazzeri; Cristina Vassalle; Alessandro Pingitore (MDPI AG, 2024)
Transitioning from childhood into adolescence is an extraordinary time of life, associated with major physical, emotional, cognitive, and social changes and characterized by dynamic development in which interaction with the environment modulates the individual resources responsible for well-being and health. This sensitive period is the time when, in addition to hormonal, metabolic, and neural changes, certain behavioral strategies begin to take shape that will shortly go on to define the emotional, social, and cultural identity of the individual. This narrative review aimed to uncover the crucial processes underlying the transition by identifying processes that are responsible for cognitive, psychosocial, and emotional development, in the absence of disease. For this aim, we highlight (1) the physical, psychological, and social determinants during the transition from childhood to adolescence; (2) the role of health-related variables in resilience or vulnerability mechanisms; and (3) recent school-based strategies to promote health and well-being. Recognizing that health and well-being are the result of the interaction of many biological, psychological, social, cultural, and physical factors will lead to comprehensive health promotion involving all actors joining the growth process, from health professionals and the educational community to parents and community. Furthermore, it is important that psychosocial dimensions are strengthened already during childhood to prevent the onset of frailty and illness in adolescence.